ANALYSIS OF THE TOURIST OFFER OF THE CITY OF ZAGREB: A TOURIST PERSPECTIVE - Alkier Tomić, Romina; Vučenović, Danijel; Milojica, Vedran (Economic Outlook, 2025)
In this paper authors to present the importance of city tourism as a specific form of tourism in the tourist offer, as well as the attitudes of tourists who chose the city of Zagreb as their holiday destination. They present the most relevant scientific findings in this topic, as well as the selected findings of the most recent study Attitudes and Expenditures of Tourists in Croatia TOMAS 2022/23. The results indicate tourists being mostly satisfied with the elements of Zagreb tourist offer, however, it is necessary to improve the quality of information provided about the destination, Internet access, etc. Improvement of marketing activities would improve the visibility and recognizability of tourist offer and potentially influence tourist´s decision-making process, stimulate them to visit, enjoy unique experiences and remain loyal to the destination.